OPTIMALISASI PRODUKSI SEMI REFINED CARAGINAN (SRC) DARI RUMPUT LAUT( Eucheuma cottonii) - Moh. Rizal; Mappiratu Mappiratu; Abd. Rahman Razak (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
ABSTRACT The investigation about the optimization of SRC Production (semi refined caraginan) from Eucheuma cottonii has beendone. The study aim to find whether or not there is interaction beetween consentration KOH and cooking time on rendamen and SRC purity degree and to find at which consentration KOH and cooking time yield the highest SRC Purity degree. It was done by applying completely randomized design (CRD) i. e factorial design. It was consist of 2 factors ( consentration KOH and cooking time ). Each factors consist of 3 levels and all of experiments where done in duplo, so the total there ware 18 experiments. The result showed that The highest Rendaman and the highset degree of piyurity were obsained at consentration KOH and cooking time were 8 % and 60 minutes respectively. The result were 33.83 and 59.243 % accordingly Keywords : Eucheuma cottonii, Extraction Semi Refined Carrageenan, KOH concentration, Long time of cooking